Radiance from Halcyon : a Utopian experiment in religion and science - Ivey, Paul Eli, 1959- (Minneapolis : University of Minnesota Press, 2013)
In May 1904, the residents of Halcyon-a small utopian community on California's central coast-invited their neighbors to attend the grand opening of the Halcyon Hotel and Sanatorium. As part of the entertainment, guests were encouraged to have their hands X-rayed. For the founders and members of Halcyon, the X-ray was a demonstration of mysterious spiritual forces made practical to human beings. Radiance from Halcyon is the story not only of the community but also of its uniquely inventive members' contributions to religion and science. The new synthesis of religi.
Chapter 8: Forces of Nature and the Electric Panacea: Healing at the Halcyon SanatoriumChapter 9: Dune Spirit, Harmony, and Dissonance: Music and Art at Halcyon; Chapter 10: The Avatar Arrives: Spiritual Fulfillment and Scientific Advancement; Conclusion; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; X; Y; Z.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Theosophy; Theosophy -- California -- Halcyon; Religion; Humanities; Religion and science; Religion; Humanities; Religion and Science; Religious Philosophies; Théosophie.; Religion; Sciences humaines; Religion et sciences; theosophy; religion (discipline); humanities; RELIGION -- Theosophy; HISTORY -- United States -- General; Religion and science; Religion; Humanities; Theosophy; California -- Halcyon